Endothelial activation and stress index for prediction of mortality in asthma - He, Yili; Li, Yang; Xiaojin, Yuan; Wu, Dan; Jiang, Wenyan; Xie, Xianlong (Frontiers in Medicine, 2025)
BackgroundEASIX (Endothelial Activation and Stress Index) has been shown to be associated with the prognosis of various diseases in numerous studies, but its relationship with short- and medium-term outcomes in asthma patients admitted to the ICU (Intensive Care Unit) remains unclear.MethodsThis retrospective cohort study included 3,737 asthma patients from the Medical Information Mart for Intensive Care-IV (MIMIC-IV) database (2008–2019). We calculated log2(EASIX) using platelet count, creatinine, and lactate dehydrogenase levels measured on ICU admission day 1. We analyzed the association between log2(EASIX) and 28-day and 60-day in-hospital mortality using multivariable Cox regression and restricted cubic splines. Proportional hazards assumptions were tested to ensure no time-dependent bias. Subgroup analyses and interaction tests were conducted to verify the stability. ROC (Receiver Operating Characteristic) analysis was performed to assess the prognostic performance of log2(EASIX).ResultsThe mean age of patients was 62.5 years, with 289 deaths at 28 days and 432 at 60 days. Higher log2(EASIX) was independently associated with increased mortality at both 28 days [hazard ratio (HR) = 1.14, 95% confidence interval (CI): 1.02–1.27, p = 0.017] and 60 days (HR = 1.13, 95% CI: 1.02–1.24, p = 0.017). The highest tertile had significantly higher mortality than the lowest tertile (28-day: HR = 1.84, 95% CI: 1.16– 2.90, p = 0.009; 60-day: HR = 1.65, 95% CI: 1.08–2.51, p = 0.019). A linear relationship was observed between log2(EASIX) and both 28-day and 60-day mortality (P for non-linearity test = 0.29 and 0.633). Subgroup analyses and interaction tests indicated that the association between log2(EASIX) and mortality was stable. The ROC curve analysis revealed AUC (Area Under the Curve) values for 28- and 60-day mortality of 0.892 and 0.881, respectively, with Youden indices of 0.63 and 0.61, indicating good predictive performance.ConclusionElevated log2(EASIX) levels are independently associated with increased in-hospital mortality in patients with asthma. Endothelial Activation and Stress Index show good predictive performance for short- and medium-term mortality in this patient population.